2018
DOI: 10.1097/ico.0000000000001501
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Cystoid Macular Edema After Descemet Membrane Endothelial Keratoplasty

Abstract: Purpose:The incidence of and risk factors for cystoid macular edema (CME) after Descemet membrane endothelial keratoplasty (DMEK) remain uncertain. This study examines the incidence of and risk factors for CME after DMEK.Methods:This retrospective, single-center study included patients with no history of CME who had undergone DMEK. Patients were examined weekly for 1 month after surgery and at 3 and 6 months after surgery. Follow-up examinations included visual acuity (VA) assessment, pachymetry, anterior segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
51
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(59 citation statements)
references
References 25 publications
6
51
1
1
Order By: Relevance
“…The incidence of CME reported here was higher than that previously reported in Caucasian eyes (7%–13.8%). 47 The increase in CME incidence might be attributed to the difference in etiology. As we previously reported, 8 bullous keratopathy from argon laser iridotomy, pseudoexfoliation syndrome, or pseudophakic bullous keratopathy are leading etiologies of DMEK in Japan, whereas the proportion of FECD is relatively lower than that in Western countries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence of CME reported here was higher than that previously reported in Caucasian eyes (7%–13.8%). 47 The increase in CME incidence might be attributed to the difference in etiology. As we previously reported, 8 bullous keratopathy from argon laser iridotomy, pseudoexfoliation syndrome, or pseudophakic bullous keratopathy are leading etiologies of DMEK in Japan, whereas the proportion of FECD is relatively lower than that in Western countries.…”
Section: Discussionmentioning
confidence: 99%
“…1,2 This complication can be observed after different ocular surgeries, including DMEK. 37 Recent studies using spectral domain optical coherence tomography (SD-OCT) have shown that the incidence of CME after DMEK is 7% to 13.8%. 47 Therefore, Heinzelmann et al 4 recommended regular SD-OCT monitoring during the first 6 months after DMEK.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…MΕ following penetrating keratoplasty is a common complication but recently with the development of new endothelial grafting techniques (Descemet’s stripping endothelial automated keratoplasty and Descemet’s membrane endothelial keratoplasty), which are supposed to be less invasive, their incidence has increased 125,126. Keratoplasty-related ME, usually, resolves spontaneously or with topical anti-inflammatory treatment alone, within a few weeks, without affecting the final visual outcome of patients 125–127…”
Section: Therapeutic Managementmentioning
confidence: 99%
“…Common complications of the early postoperative period following DMEK surgery are transplant detachment (4.0-34.6%) [14][15][16], early postoperative failure (1.4-5.0%) [5,17], and macular edema (DMEK-ME, 1.0-15.6%) [18][19][20][21][22][23], the latter peaking between 1 and 3 months after surgery [18][19][20][21]23].…”
Section: Introductionmentioning
confidence: 99%